The transatlantic world of Charles Stewart Parnell (1846–91)†. (2nd July 2016) - Whelan, Bernadette
Abstract : This article explores the transatlantic world of Charles Stewart Parnell, leader of the Irish home rule and land reform movements and the Irish Parliamentary Party in the parliament of the United Kingdom of Great Britain and Ireland at Westminster between 1877 and 1891. Based on hitherto unused sources and reviewing existing material, it adopts a longer timeframe than previous studies. The American heritage of the Parnell family is examined, in particular how their American relatives, the forebears of Parnell's mother Delia Stewart, engaged with the emerging American republic. It reveals how a transatlantic familial network became an intrinsic part of Charles Stewart Parnell's political and social world, influencing his rhetorical and political stance on Ireland's destiny. Parnell's transatlantic links provide an important key to understanding both his political outlook and his sense of personal identity.